Gettysburg 1863 : high tide of the Confederacy - Smith, Carl, 1946- (London : Osprey Military, 1998)
This study examines one of the decisive battles of the American Civil War (1861-1865). The Confederate invasion of the Northern states was General Lee's last great gamble. By taking the war to the Union Lee hoped to force Lincoln into peace negotiations, or win support from the European powers who were watching events closely from across the Atlantic. Equally, Meade's Army of the Potomac needed to regain its fighting credibility after the setbacks of Fredericksburg and saw this as an opportunity to redeem its honor. The clash of 150,000 soldiers from both sides would ultimately decide the fate of a nation.
Origins of the campaign -- Opposing commanders -- The opposing armies -- Gettysburg : day one -- Day two -- Day three -- Day four : 4th of July -- Gettysburg today -- Wargaming Gettysburg.
Includes bibliographical references.
Keywords: 1861-1865; Gettysburg Campaign, 1863.; Gettysburg, Battle of, Gettysburg, Pa., 1863.; Campagne de Gettysburg, 1863.; Bataille de Gettysburg, Gettysburg, Penns., 1863.; Military campaigns; History